Implementasi Supply Chain Management Pada Graha Phone Service Berbasis Web - Harahap, Faisal; Amanda Putri, Raissa; Hasyifah Sibarani, Fathiya (Universitas Islam Balitar, 2024)
Graha Phone Service Store, which is engaged in the sale and repair of mobile phone devices, faces various challenges in stock management and spare part distribution. The problems faced include sub-optimal stock management, which can lead to overstocks or shortages, uncoordinated distribution, as well as less than optimal information on goods between stores and suppliers. To overcome these problems, a web-based Supply Chain Management (SCM) implementation is needed. SCM will help manage the flow of goods, information, and services efficiently from suppliers to consumers. This research aims to develop a web-based SCM system to digitally manage spare part stock, enable integration of store inventory with real-time supplier stock management, and build better communication between stores and suppliers. Based on the research results, this system can optimise supply chain management and improve customer satisfaction through better service